Health impact assessment needs in south-east Asian countries - Caussy Deoraj; Kumar Priti; Than Sein U. (The World Health Organization, 2003)
A situation analysis was undertaken to assess impediments to health impact assessment (HIA) in the South-East Asia Region of WHO (SEARO). The countries of the region were assessed on the policy framework and procedures for HIA, existing infrastructure required to support HIA, the capacity for undertaking HIA, and the potential for intersectoral collaboration. The findings show that environmental impact assessment (EIA) is being used implicitly as a substitute for HIA, which is not explicitly or routinely conducted in virtually all countries of the Region. Therefore, policy, infrastructure, capacity, and intersectoral collaboration need strengthening for the routine implementation of HIA.